2014
DOI: 10.1121/1.4868369
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating to new ears: The effects of sensory and sensory-motor feedback

Abstract: Changing the shape of the outer ear using small in-ear molds degrades sound localization performance consistent with the distortion of monaural spectral cues to location. It has been shown recently that adult listeners re-calibrate to these new spectral cues for locations both inside and outside the visual field. This raises the question as to the teacher signal for this remarkable functional plasticity. Furthermore, large individual differences in the extent and rate of accommodation suggests a number of fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 44 publications
6
72
0
Order By: Relevance
“…More recently, the role of sensorimotor calibration of audition emerges as very significant (Aytekin et al, 2008; Boyer et al, 2013; Carlile and Blackman, 2013; Carlile et al, 2014). Here we provide data attesting that when humans can use sensorimotor information, their spatial map of an auditory space is very accurate.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the role of sensorimotor calibration of audition emerges as very significant (Aytekin et al, 2008; Boyer et al, 2013; Carlile and Blackman, 2013; Carlile et al, 2014). Here we provide data attesting that when humans can use sensorimotor information, their spatial map of an auditory space is very accurate.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that the adult human brain can adapt to altered cues for sound direction. This has been demonstrated in studies using ear plugs 36,38 as well as molds inserted in the pinnae [16][17][18] . Some recent studies have also demonstrated a learning effect using visual positional feedback delivered via a head-mounted display.…”
Section: Discussionmentioning
confidence: 84%
“…There is increasing evidence that the adult brain is more adaptable than classically thought 15 . For example, it has been demonstrated that this adaptability (or plasticity) can lead to a decrease in localization error over time when a listener's normal cues for sound location are disrupted by physically altering the shape of the ear using molds [16][17][18] . However, this process typically takes place over the course of days or weeks (for a review see Mendonça et al 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of characteristics have been studied, ranging from the just-noticeable-differences in localization accuracy, adaptation, and learning effects, to the influence of the source's spectral content and room reflections [1][2][3]. Recent experiments also studied the contribution of high frequency content in the presence of a noise masker [4], the degradation of localization accuracy with outer ears occlusions [5] and bilateral hearing aids [6], and the localization of multiple coherent sound sources [7].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects are typically asked to indicate the direction of the perceived sound source by (a) reporting the closest loud-speaker, fixed acoustic pointer or label [7,4,2]; (b) steering a movable pointer [8]; (c) reporting the direction on a graphical user interface (GUI) or on paper [6]; or (d) turning their face toward the perceived sound source after the stimulus has been presented [9,5]. This paper is concerned with experiments where subjects report the position of the perceived sound source by turning toward it while the stimulus is being presented.…”
Section: Introductionmentioning
confidence: 99%